2020
DOI: 10.1111/ijlh.13308
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of mortality prediction accuracy in critically ill patients through combination of SOFA and APACHE II score with markers of stress haematopoiesis

Abstract: Assessment of organ failure and mortality risk in critically ill patients is possible through Systemic Organ Failure Assessment (SOFA) and APACHE II scores. According to the results of prospective studies, 1-3 higher SOFA score is associated with increased mortality. APACHE II score is based on 17 physical and laboratory parameters as well as from data on personal history. 4,5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Similar to previous studies in patients undergoing HCT 11,12 and other critically ill patients, [1][2][3][4][5][6][7] erythroblastosis is a predictor of early mortality in adult patients who underwent single-unit CBT.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Similar to previous studies in patients undergoing HCT 11,12 and other critically ill patients, [1][2][3][4][5][6][7] erythroblastosis is a predictor of early mortality in adult patients who underwent single-unit CBT.…”
Section: Discussionsupporting
confidence: 67%
“…Erythroblasts (EBLs), also known as nucleated red blood cells, are progenitor cells of erythroid lineage and are not typically detected in peripheral blood (PB) under steady‐state conditions; however, EBLs have been observed in PB during a variety of serious conditions, such as critically ill status, 1‐7 neonatal disorders, 8‐10 sepsis, 2,6,8,9 and post‐hematopoietic cell transplantation (HCT) 11,12 . Several studies have indicated that the presence of higher levels of EBLs in PB may adversely affect survival in patients with serious conditions, including allogeneic HCT 1‐7,10‐12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, our study is the first to demonstrate the predictive value of NRBCs at a single measurement point at hospital admission. Previous studies from the ICU setting have classified patients into NRBC positive or negative by using NRBC results from the whole ICU stay and, in some cases, analyzed the predictive value using the highest NRBCs during the ICU stay ( 10 , 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, circulating NRBCs can be measured reliably by some automated hematology analyzers at very low concentrations ( 11 ), and this development has opened renewed interest in NRBCs as a potential prognostic biomarker. Studies have described an association between circulating NRBCs and mortality in ICU patients ( 10 , 12 , 13 ), mortality after hospital discharge for ICU patients ( 14 ), and for mortality in ICU patients with surgical sepsis ( 15 ) and ARDS ( 16 ). However, most of these studies have analyzed the highest NRBC value found during the admittance, which is not necessarily useful as a predictor early in the admission.…”
mentioning
confidence: 99%